Improving optical properties of in situ reduced graphene oxide/poly(3-hexylthiophene) composites. (23rd February 2017) - Bakour, Anass; Baitoul, Mimouna; Bajjou, Omar; Massuyeau, Florian; Faulques, Eric
Abstract: Poly(3-hexylthiophene) (P3HT)-graphene nanocomposites were successfully prepared by an in situ reduction of graphene oxide (GO). The main goal of this work was to investigate the changes introduced by the insertion of reduced GO (RGO) in the conjugated polymer P3HT on the optical and structural properties of the composites at different weight ratios. Raman scattering and Fourier transform Infrared spectroscopies were primarily used to investigate reduction efficiency of GO sheets by hydrazine, and then to examine the nature of bonds between the components of the composites. The degree of homogeneity was investigated by means of scanning and transmission electron microscopies. The UV–Vis absorption spectroscopy results obtained from the different film samples confirm the existence of an electronic interaction inside the composites, as well as a decrease in the bandgap of the composite films. Steady-state photoluminescence (PL) exhibits strong quenching after increasing RGO wt%. Moreover, time resolved PL shows a decrease in the mean lifetime of photogenerated excitons. Our study reveals the existence of charge/energy transfer at the interface between P3HT and in situ RGO at low concentrations, leading to an overall enhancement of optical properties which makes such composites promising candidates for photovoltaic applications.